Law Enforcement on Ordinary Crimes in Minor Motive using Restorative Justice: Perspective Criminal Law Reform - Jonlar Purba (The Southeast Asia Law Journal, 2016)
The disparity by judges in decisions led to the inability of people facing criminal offenses. Laws are not grounded to small communities, the judicious use of a crime in Indonesia as well as the strength of spider webs in which only able to ensnare minor crimes, but are not able to touch the major crimes that occurred in Indonesia. This study uses normative juridical. The results of this study found that completion ordinary crime patterned petty can be reached with a restorative justice approach, so it can focus on the direct participation of the offender, victim and community.